NaFeS2 as a new photocatalytic material for the degradation of industrial dyes. Issue 4 (August 2020) - Dileepkumar, V.G.; Surya, P.S.; Pratapkumar, C.; Viswanatha, R.; Ravikumar, C.R.; Anil Kumar, M.R.; Muralidhara, H.B.; Al-Akraa, Islam M.; Mohammad, Ahmad M.; Chen, Zhong; Bui, Xuan-Thanh; Santosh, Mysore Sridhar
Graphical abstract: Highlights: NaFeS2 is used as a new photocatalyst. Degradation of methylene blue (MB) and indigo carmine (IC) dyes have been investigated. NaFeS2 has an energy band gap of 2.01 eV. Electrochemical studies also complement the photocatalytic activity. This material could be extended for the treatment of various emerging pollutants as well. Abstract: A new photocatalytic material sodium iron disulfide (NaFeS2 ) has been synthesized via a hydrothermal method for the degradation of methylene blue (MB) and indigo carmine (IC). This material has been subjected to various analytical, electrochemical and photocatalytic studies to understand its morphology, crystallinity, band gap, oxidation-reduction potential and ability to catalyse the rate of dye degradation. The material exists as nanorods with a thickness of 30–100 nm and a monoclinic phase with an average crystallite size of 25–30 nm. The energy bandgap of the prepared photocatalyst has been calculated using the Kubelka-Munk function and is found to be 2.01 eV. Using a UV light source, the photocatalytic activity of NaFeS2 has been carried out, where the time of irradiation determined the ability of the catalyst to degrade the dye under investigation. With a degradation efficiency of 97% in 105 min for MB and 99% in 45 min for IC, NaFeS2 appears as an excellent photocatalytic material. The electrochemical studies also act as a testament for NaFeS2 'sadmirable photocatalytic property. The photocatalytic and electrochemical activities of NaFeS2 offer an innovative platform for the treatment of various other environmental pollutants as well.